Essential oils of Citrus limon, Piper aduncum and Mentha spicata: Antioxidant properties and specific applications in industry - Cueva Ríos, María Alina (2023)
This study focuses on the antioxidant properties and industrial applications of essential oils from lemon (Citrus limon), matico (Piper aduncum), and spearmint (Mentha spicata). The study was descriptive and based on a literature review of research between 2017 and 2023, using the PRISMA methodology for the selection of studies. It was found that Citrus limon essential oil is notable for its high proportion of monoterpene hydrocarbons and d-limonene, effective in neutralizing free radicals and combating premature skin aging, and has applications in aromatherapy, the food industry, cosmetics, and pharmaceuticals. It was also found that Piper aduncum oil, rich in dillapiole, exhibits anti-inflammatory activity, although its antioxidant activity is low compared to other standards, it has applications in alternative medicine, sustainable agriculture, and as a biopesticide. On the other hand, Mentha spicata essential oil, rich in oxygenated monoterpenes and phenolic compounds, protects against oxidative damage, is effective in the treatment of diseases related to oxidative stress, and is used in the food and pharmaceutical industry. This article concluded by highlighting the importance and versatility of these essential oils in various sectors, from health and wellness to the food and cosmetic industry, underscoring the relevance of continuing to research their properties and applications.